Analis Resiko Keselamatan dan Kesehatan Kerja Pada Petugas Kebersihan di Rumah Sakit - Catur Yuantari; Hafizhatun Nadia (Universitas Faletehan, 2018)
Work at hospital is likely risking get diseases transmission from patients. The risk is not potential to medical staff only, but also nonmedical staff such as cleaning staff. Along doing the work, risk that always faces by cleaning staff are biological factor and chemical such as bleaching. The purpose of the study was to analyze the risk of work health and safety of cleaning staff in Tugurejo hospital Semarang. This study was descriptive analytic study, risk identification assessed with job safety analysis (JSA), data collection had been done with observational and interview. Result showed that the risk faces by cleaning staff was bacteria exposure, bacteria and virus and medical chemotherapy exposure that classified as high risk (36,6%). The risk of impaled needle and scratched sharp object, slipper, musculoskeletal problem, fall from stairs, and electric shock classified as moderate risk (45,1%). Allergic risk or irritation through chemical uses classified as low risk (18,3%). To prevent the risks, suggested to cleaning staff to use personal protection equipment whenever and wherever in doing the job. While, need to evaluate on kind of personal protection equipment that used by cleaning staff especially conformity kind personal protection equipment with the occupation.